Cost-effective fabrication of photopolymer molds with multi-level microstructures for PDMS microfluidic device manufacture. Issue 7 (23rd January 2020) - Olmos, Carol M.; Peñaherrera, Ana; Rosero, Gustavo; Vizuete, Karla; Ruarte, Darío; Follo, Marie; Vaca, Andrea; Arroyo, Carlos R.; Debut, Alexis; Cumbal, Luis; Pérez, Maximiliano S.; Lerner, Betiana; et al.
Abstract : This paper describes a methodology of photopolymer mold fabrication with multi-level microstructures for polydimethylsiloxane (PDMS) microfluidic device manufacture. Abstract : This paper describes a methodology of photopolymer mold fabrication with multi-level microstructures for polydimethylsiloxane (PDMS) microfluidic device manufacture. Multi-level microstructures can be performed by varying UVA exposure time and channel width. Scanning Electron Microscopy (SEM), Atomic Force Microscopy (AFM) and profilometry techniques have been employed to characterize the molds. Multiple molds with multi-level microstructures can be formed in a unique piece. Overall height/depth of the structures reaches up to 677 μm and a minimum of 21 μm. The method provides several advantages such as reduction of fabrication time, multiple structures with diverse topologies, a great variety of depth and height in a single mold and low cost of fabrication. The effectiveness of multi-level microstructure fabrication was evaluated by constructing PDMS microfluidic devices for cell culture and proliferation.